2014
DOI: 10.1074/jbc.m114.557843
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Biophysical Characterization of Murine Rif1 C Terminus Reveals High Specificity for DNA Cruciform Structures

Abstract: Background: Mammalian Rif1 is a regulator of DNA replication timing and repair. Results: We characterized DNA binding by Rif1 C terminus and identified the critical residues. Conclusion: Rif1 shows a highly selective binding of DNA cruciform structures. Significance: This is a step forward in the understanding of Rif1 functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 41 publications
(35 reference statements)
2
33
0
Order By: Relevance
“…6b, lane 5). The DNAbinding domain of mammalian Rif1 has been reported to bind to structured DNAs including forked DNA, flap DNA and cruciform structures 31,32 . Therefore, we prepared various structured DNAs and used them in competition assays with the G 24 DNA, which is known to form a parallel-type G-quadruplex structure 33 .…”
Section: Purified Rif Protein Binds To G-quadruplex Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…6b, lane 5). The DNAbinding domain of mammalian Rif1 has been reported to bind to structured DNAs including forked DNA, flap DNA and cruciform structures 31,32 . Therefore, we prepared various structured DNAs and used them in competition assays with the G 24 DNA, which is known to form a parallel-type G-quadruplex structure 33 .…”
Section: Purified Rif Protein Binds To G-quadruplex Structuresmentioning
confidence: 99%
“…Duplex DNA, Y-fork DNA, A-fork (5′) DNA (3′-flap DNA), A-fork (3′,5′) DNA (fork DNA) and cruciform DNA were generated by oligonucleotide annealing, as described in ref. 32. Various combinations of oligonucleotides were mixed in 10 mM Tris-HCl, pH 7.5, and 1 mM EDTA, heated at 98 °C for 4 min and cooled to room temperature.…”
Section: Competing Financial Interestsmentioning
confidence: 99%
“…The Stokes radius ( R S ) of each TALE was estimated using the elution time with reference to a standard globular protein set (GE Healthcare)27. The experimental conditions used for the chromatography were the same as described in the sample preparation.…”
Section: Methodsmentioning
confidence: 99%
“…The HiLoad 26/600 Superdex 200 pg column was calibrated with a Gel Filtration Protein Calibration Kit (GE Healthcare) at a linear flow rate of 1 ml/min. The protein standards were as follows: Aprotinin ( M W : 6.5 kDa, R S : 13 Å), Ribonuclease A ( M W : 13.7 kDa, R S : 16 Å), Carbonic anhydrase ( M W : 29.0 kDa, R S : 20 Å), Ovalbumin ( M W : 44.0 kDa, R S : 30 Å), and Conalbumin ( M W : 75.0 kDa, R S : 36 Å)27. The gel-phase distribution coefficient, K av , for each protein was calculated using the equation K av  = ( V e  −  V 0 )/( V c  −  V 0 ), where V e is the elution volume for the protein, V 0 is the column void volume determined using blue dextran 2000 (GE Healthcare) monitored at a wavelength of 280 nm, and V c is the geometric column volume (320 ml).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, they showed that CRII binds cruciform DNA with high selectivity and is therefore a DNA binding domain. 43 In a point of view article in Epigenetics, GonzalezRomero and Ausio discuss the unusual histone H1 variant in Drosophila, called dBigH1. 44 They state that, despite the presence of unusual acidic amino acid patches at the N-terminal end of dBigH1, in contrast to the arginine patches at the N-and C-terminal domains of other histone H1 proteins, the essential requirements of H1 proteins appears to be the presence of a lysine-and alanine-rich intrinsically disordered C-terminal domain.…”
Section: Analyzing Functions Of Idps and Idprsmentioning
confidence: 99%